2011
DOI: 10.1063/1.3629773
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical properties of Al0.9Sc0.1N thin films evaluated at 2.5 GHz film bulk acoustic resonators

Abstract: AlN films are employed in RF filters for wireless communication. We report on enhanced coupling factors kt2 obtained by partial substitution of Al by Sc. Al0.88Sc0.12N films were deposited by reactive magnetron sputtering from an Al0.9Sc0.1 alloy target. They grew in the piezoelectric wurtzite phase with a similar microstructure as pure AlN films. The clamped d33,f increased considerably from 5.1 to 7.8 pm/V. The admittance measured at thin film bulk acoustic wave resonators was fitted to an equivalent circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(55 citation statements)
references
References 12 publications
3
51
0
1
Order By: Relevance
“…It is chemically and high-temperature stable, and is known for its low acoustic losses, high Q values as well as the highest piezoelectric constant (e 33 =1.46 C/m 2 ) among group III nitride semiconductors [2]. Recently, studies on alloying AlN with ScN reported a significant increase in the piezoelectric response and electromechanical coupling [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is chemically and high-temperature stable, and is known for its low acoustic losses, high Q values as well as the highest piezoelectric constant (e 33 =1.46 C/m 2 ) among group III nitride semiconductors [2]. Recently, studies on alloying AlN with ScN reported a significant increase in the piezoelectric response and electromechanical coupling [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…6-7%), can be attributed to the low piezoelectric constant, e 33 , of the PVD-AlN thin-film itself. Recent studies have demonstrated that the piezoelectric coefficient of PVD-AlN films can be increased by alloying with scandium (Sc), [245,246] or by co-doping of AlN using Mg-Zr or Mg-Hf. [247] However, the process of doping PVD-AlN has other drawbacks that degrade the Q-factor of the resonator.…”
Section: Electromechanical Filtersmentioning
confidence: 99%
“…A 400% increase in piezoelectric response for x=0.43 [1] as well as an improved electromechanical coupling (kt 2 ) [2][3][4][5] make this material a potential alternative to the commonly used pure AlN in telecommunication industry [6]. The anomalously large piezoelectric modulus d33 of ScxAl1-xN was proposed to be related to softening of the material caused by a competition between Sc and Al atoms for the bonding coordination of nitrogen, due to a metastable layered hexagonal phase of ScN [7].…”
Section: Introductionmentioning
confidence: 99%